Cough is less common and less severe in systemic sclerosis‐associated interstitial lung disease compared to other fibrotic interstitial lung diseases. Issue 8 (23rd May 2017) - Cheng, Jasmine Z.; Wilcox, Pearce G.; Glaspole, Ian; Corte, Tamera J.; Murphy, Darra; Hague, Cameron J.; Ryerson, Christopher J.
ABSTRACT: Background and objective: The objectives of this study were to determine the prevalence and characteristics of cough in idiopathic pulmonary fibrosis (IPF), chronic hypersensitivity pneumonitis (HP) and systemic sclerosis‐associated interstitial lung disease (SSc‐ILD). Methods: Cough severity was measured in consecutive patients with IPF ( n = 77), HP ( n = 32) and SSc‐ILD ( n = 67) using a 10‐cm visual analogue scale (VAS). Dyspnoea and quality of life were measured using established questionnaires. Cough severity was compared across ILD subtypes and predictors of cough severity were determined using multivariate analysis. Results: Cough was more common in IPF and chronic HP compared to SSc‐ILD (87% and 83% vs 68%, P = 0.02). The median (interquartile range) VAS score was 39 (17–65) in the IPF cohort, 29 (11–48) in HP and 18 (0–33) in SSc‐ILD ( P < 0.0001). Cough was more often productive in chronic HP and IPF (63% and 43% vs 21%, P < 0.001). Cough severity was independently predicted only by ILD diagnosis and higher dyspnoea score. Cough severity was not associated with other common causes of cough. Cough was a significant predictor of quality of life in IPF and SSc‐ILD with adjustment for age, sex, dyspnoea and ILD severity; however, cough was not associated with quality of life in chronic HP. Conclusion: Cough is more frequent, more severe and more often productive in IPF and chronic HP compared to SSc‐ILD, despite similar ILD severity in these cohorts. Cough severity is strongly and independently associated with dyspnoea and pulmonary function, and is a significant contributor to reduced quality of life in both IPF and SSc‐ILD. Abstract : See related Editorial Cough is more common, more severe and more often productive in idiopathic pulmonary fibrosis (IPF) and chronic hypersensitivity pneumonitis (HP) compared to systemic sclerosis‐associated interstitial lung disease (SSc‐ILD), despite similar ILD severity. Cough severity is independently associated with dyspnoea, is not associated with other common causes of cough in ILD and is an independent predictor of quality of life.